Respostas

2014-05-13T16:45:12-03:00
(a-b)⁻¹ . √c

a) a=1/4, b=-1/4. =1/4
(a - b)⁻¹ . √c

   1
-------- . √c
(a - b)⁺¹

      1
 ------------..  √1/4
  1      1    
--- -(- ---) .
  4      4


      1
 ------------.  √1/4
   1       1
----- + ---- 
   4       4

       1        1                   4      1         4
    ---------. ---       = 1 x -----.  ---- = -----   = 1
       2        2                    2      2        4 
     ----
       4

b)  1
-------- . √c    a= -1/4, b= 1/4 c= 1/4
(a - b)⁺¹

      1
------------ .√1/4
(-1/4 -1/4)


    1          1            4          1          4
---------x  -----  = -  ----- x  ----- = -  --- = - 1
 -2/4         2            2           2         4

c) 1
-------- . √c      a=0,25 b= - 0,25 c= 0,25
(a - b)⁺¹

     1
---------------- .√0,25
(0,25 -(0,25))

     1
--------------  . 0,5
(0,25 + 0,25)

    1               0,5
-------. 0,5 =  ------ = 1
  0,5             0,5

d)  1
-------- . √c        a=0,25  b= - 0,25 c = 0,25
(a - b)⁺¹

       1
---------------- .√0,25
(-025 - 0,25)


       1                    0,5
----------- . 0,5 = --------- = - 1
     - 0,5                -0,5


e)  1
-------- . √c      a= 4/9   b= -4/9 c=4/9
(a - b)⁺¹

   1
-------------- . √4/9
(4/9 -(-4/9)

      1
------------- . 2/3    
(4/9+4/9)

      1                      9     2      18        3
---------. 2/3  =  1x-----x---- = ----- = ------ = 3/4
     8/9                     8    3       24        4

f)  1
-------- . √c    a= -4/9   b= 4/9    c=4/9
(a - b)⁺¹


     1
------------ .√4/9
(-4/9 -4/9)

     1                           9      2        18          3
------------x 2/3   = 1x ---- x---- =  ------- =  ---- =  -  3/4
   -8/9                        - 8      3     - 24       - 4